Characterization of Anti-Cancer Activities of Violacein: Actions on Tumor Cells and the Tumor Microenvironment - Dahlem, Charlotte; Chanda, Shilpee; Hemmer, Jan; Schymik, Hanna S.; Kohlstedt, Michael; Wittmann, Christoph; Kiemer, Alexandra K. (Frontiers in Oncology, 2022)
Natural products have been shown to serve as promising starting points for novel anti-cancer drugs. In this study, the anti-cancer activities of the purple compound violacein, initially isolated from Chromobacterium violaceum, were investigated. To highlight the crucial role of the tumor microenvironment on the effectiveness of cancer therapies, this study includes effects on macrophages as prototypic cells of the microenvironment in addition to the investigation of tumor-centric activities. Using 2D and 3D cell culture models, automated live-cell microscopy, and biochemical analyses, violacein was demonstrated to inhibit tumor cell proliferation and migration. The violacein-triggered tumor cell death was further associated with caspase 3-like activation and ATP release. Stimuli released from dead cells resulted in inflammatory activation of macrophages, as shown by NF-κB reporter cell assays and macrophage morphology analysis. Moreover, macrophages deficient in the inflammasome component Nlrp3 were found to be significantly less sensitive towards treatment with violacein and doxorubicin. Taken together, this study provides new insights into the biological activity of violacein against cancer. In addition, the in vitro data suggest immunogenic features of the induced cell death, making violacein an interesting candidate for further studies investigating the compound as an inducer of immunogenic cell death.